S7.4 Cost-effectiveness of targeted HIV preventions for female sex workers: an economic evaluation of the Avahan programme in Southern India. (10th July 2011) - Chandrashkar, S; Vassall, A; Guinness, L; Pickles, M; Reddy, B; Shetty, G; Boily, M C; Lowndes, K; Alary, M; Vickerman, P
Abstract : Objective(s): The aim of the presentation paper is to assess the cost-effectiveness of HIV prevention interventions for female sex workers in India, in the context of large-scale programme effort, the Avahan Programme. Design/methods: We estimate cost-effectiveness using comprehensive measurements of cost; and, impact estimates based on dynamical transmission models of HIV and STI transmission that are fitted to observed prevalence trends. Our primary outcome measure is incremental cost per DALY averted (ICER) for the HIV prevention programme compared to a "do-nothing" base case. Results: In 2007, the implementing NGO cost per person reached at least once in a year ranges from US47 to US154. When all costs are taken into account (including expertise enhancement, management and contracting costs), the cost per person reached increases to US112 to US 213, depending on location and year. Median incremental costs per infection averted range from US 876 (370, 3040) to US2574 (1344, 7132). Median incremental costs per DALY averted range from US49 (20 171) in to US 143 (74, 388). These costs per DALY may increase as results from other states are included. Conclusions: This study presents robust evidence that demonstrates that HIV prevention interventions targeted at high risk vulnerable groups can achieve substantial reductions in HIV infections at an acceptable cost in a concentrated epidemic setting. Moreover, we demonstrate cost-effectiveness in the context of a programme that is delivering HIV prevention at scale. However, the achievement of cost-effectiveness varies by setting. Our findings suggest that those responsible for HIV programmes should therefore consider funding targeted HIV prevention programmes at high risk groups in India and beyond, but should take into account setting specific drivers of the HIV epidemic.